2023
DOI: 10.3390/antibiotics12040764
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inflammation on Voriconazole Exposure in Critically ill Patients Affected by Probable COVID-19-Associated Pulmonary Aspergillosis

Abstract: (1) Background: To explore the impact of the degree of inflammation on voriconazole exposure in critically ill patients affected by COVID-associated pulmonary aspergillosis (CAPA); (2) Methods: Critically ill patients receiving TDM-guided voriconazole for the management of proven or probable CAPA between January 2021 and December 2022 were included. The concentration/dose ratio (C/D) was used as a surrogate marker of voriconazole total clearance. A receiving operating characteristic (ROC) curve analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Furthermore, more research is needed to describe the relationship between inflammation biomarkers, i.e., the host’s immune response, PK/PD parameters and TDM, more precisely. Gatti et al has shown that inflammation reflected in high plasma CRP and PCT concentrations may down-regulate the metabolism of voriconazole in patients with COVID-19-associated aspergillosis, resulting in potentially toxic voriconazole concentrations [ 43 ]. In antibiotics, exposure–response relationships using modelling approaches have been described in pharmacodynamics of vancomycin and CRP in adults [ 44 ], of teicoplanin and CRP in neonates [ 45 ] or in animal studies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more research is needed to describe the relationship between inflammation biomarkers, i.e., the host’s immune response, PK/PD parameters and TDM, more precisely. Gatti et al has shown that inflammation reflected in high plasma CRP and PCT concentrations may down-regulate the metabolism of voriconazole in patients with COVID-19-associated aspergillosis, resulting in potentially toxic voriconazole concentrations [ 43 ]. In antibiotics, exposure–response relationships using modelling approaches have been described in pharmacodynamics of vancomycin and CRP in adults [ 44 ], of teicoplanin and CRP in neonates [ 45 ] or in animal studies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%